Professional Competencies of Library Staff Engaged in Information and Analytical Support of Researches - M. A. Peksheva (Библиосфера, 2022)
The analysis of professional competencies of information specialists in domestic libraries operating in the research environment is carried out. The research is based on a questionnaire on the relevance of certain groups of professional competencies: background knowledge and skills, knowledge and skills in the field of scholarly communication, “soft” skills. The target group of the survey included library staff engaged in information and analytical support of fundamental researches of the Russian Academy of Sciences. It is revealed that the overwhelming majority of respondents recognize the relevance of the competencies included in the survey for library practice. Based on the respondents’ responses, competencies are divided into two key categories: universal and specialized. More than 60   % of the competence groups in the sections “background knowledge and skills” and “knowledge and skills in the field of scholarly communication” are classified by the majority of respondents as specialized ones. Almost all “soft” skills are classified by the majority of respondents as universal ones. Competence groups classified as “universal” can be used as the basis for the development of a general competence model for scientific library staff working in a research environment. Competence groups classified as “specialized” – are of importance for the development of variable models of competencies for individual functional roles of employees engaged in information and analytical support of scientific research.